2005
DOI: 10.1080/09593332608618540
|View full text |Cite
|
Sign up to set email alerts
|

Solar Photocatalytic Oxidation of Pretreated Wastewaters: Laboratory Scale Generation Of Design Data for Technical-scale Double-skin Sheet Reactors

Abstract: Batchwise heterogeneous photocatalytic oxidation of model wastewater (solutions of the azo dye "Acid Orange 7" in tap water) has been performed in a laboratory-scale stirred vessel reactor with non-submerged UV-A lamps using titanium dioxide "P25" as photocatalyst. Comparison to results of solar pilot-scale Plexiglass double-skin sheet reactor (DSSR) experiments indicates that the lab-scale method may predict area demand for technical-scale DSSR design. Characteristic UV-A fluences leading to TOC or COD reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…The pH was between 7 and 8. Alkalinity and phosphate concentrations were not determined, but other samples from the same source exhibited 320-335 mg L À1 CaCO 3 and about 3 mg L À1 PO 4 3À -P, resp., while their TOC concentrations were between 4.9 and 6.4 mg L À1 [14].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The pH was between 7 and 8. Alkalinity and phosphate concentrations were not determined, but other samples from the same source exhibited 320-335 mg L À1 CaCO 3 and about 3 mg L À1 PO 4 3À -P, resp., while their TOC concentrations were between 4.9 and 6.4 mg L À1 [14].…”
Section: Resultsmentioning
confidence: 99%
“…As photolysis, i.e. TOC removal by UV-A irradiation of biologically treated greywater in the absence of photocatalyst, was minute in previous experiments [14], no control experiments (UV irradiation without PAC and TiO 2 ) were performed in this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, photocatalytic disinfection potential should also be taken into consideration when talking about greywater containing various types of microorganisms in significant concentrations. Referring to a literature survey on photocatalytic treatment of greywater, it was found that almost all studies emphasized removal of organic matter content rather than simultaneous removal of organic matter and bacteria [5,22]. Through the literature, only Sanchez and co-workers were the ones who checked both organic matter content and bacterial removal in greywater by TiO 2 photocatalysis and they concluded that complete removal of bacteria was achieved in hotel greywater.…”
Section: Introductionmentioning
confidence: 99%